2014
DOI: 10.12932/ap0443.32.4.2014
|View full text |Cite
|
Sign up to set email alerts
|

Food allergens affect the intestinal tight junction permeability in inducing intestinal food allergy in rats

Abstract: Our data suggested that the allergy sensitization rate of Ovalbumin (OVA) in the juvenile group is higher than in adults and food allergens may increase intestinal mucosal permeability through intestinal tight junction regulation in inducing intestinal food allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 34 publications
2
19
1
2
Order By: Relevance
“…The significance of the similar findings in the pig system compared with our recent study in rat regarding claudin-4 and barrier properties (Markov et al, 2016 ) strongly suggests that a major common denominator has now been identified on both, protein and mRNA level. The pig system closely resembles the human intestine and therefore is a useful model for studying the detailed principles of PP FAE function and regulation in barriology and immunology, which are currently being discussed in the context of formula feeding and food allergies (Chen et al, 2014 ; Wu et al, 2015 ; Yeruva et al, 2016 ). However, as a refinement, current limitations regarding the visualization of co-localization and the quantification of immunohistological images might be overcome in epithelial monolayer and co-culture models.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of the similar findings in the pig system compared with our recent study in rat regarding claudin-4 and barrier properties (Markov et al, 2016 ) strongly suggests that a major common denominator has now been identified on both, protein and mRNA level. The pig system closely resembles the human intestine and therefore is a useful model for studying the detailed principles of PP FAE function and regulation in barriology and immunology, which are currently being discussed in the context of formula feeding and food allergies (Chen et al, 2014 ; Wu et al, 2015 ; Yeruva et al, 2016 ). However, as a refinement, current limitations regarding the visualization of co-localization and the quantification of immunohistological images might be overcome in epithelial monolayer and co-culture models.…”
Section: Discussionmentioning
confidence: 99%
“…Juvenile rats exhibit a higher Ovalbumin sensitization rate compared to adult rats possibly by increasing permeability of intestinal tight junctions. [30] It is highly likely that the differences in food allergen sensitization between the adults and the children could be due to allergens related factors capable of interfering with tight junction permeability in the gut. Age-related intestinal barrier dysfunction observed in rats is characterized by mucosal atrophy, tight junction damage with decreased epithelial tight junction protein and increased intestine bacteria counts may also be an important factor in determining allergen sensitization among children and adults.…”
Section: Discussion:-mentioning
confidence: 99%
“…(1) Remoção dos alimentos contendo os alérgenos alimentares de interesse, aqueles de difícil digestão e que contêm pesticidas, além dos aditivos alimentares, dentre esses os polissorbatos, emulsificantes (como CMC), metabissulfito de sódio e fosfato de sódio. Todos esses aditivos podem provocar alteração das tight junctions e levar ao aumento da permeabilidade intestinal, o que contribui para a quebra da tolerância de mucosa 32,[39][40][41][42] ;…”
Section: Como Induzimos Na Prática Clínica a Tolerância De Mucosa Parunclassified
“…Essa correção pode ser realizada através da utilização de complexo de enzimas e tinturas fitoterápicas que melhorem a secreção de HCl e conscientização dos pacientes quanto ao uso dos medicamentos da classe dos prazóis [44][45][46] . Importante atentar para a possibilidade de super crescimento bacteriano ou fúngico, que também deverá ser corrigida para melhora do processo alérgico 42,47 ;…”
Section: Como Induzimos Na Prática Clínica a Tolerância De Mucosa Parunclassified